Effect Of Membrane Selectivity And Configuration On Purity And Recovery Of Methane From Selected Landfill Bio-Gas - Hiew, Yen Kei (Universiti Sains Malaysia, 2021)
This thesis developed a simulation membrane model for methane enrichment from selected landfill biogas. The simulation was used to investigate the impact of methane feed composition, feed pressure, and stage cut on methane purity and recovery, as well as the impact of selectivity on methane and carbon dioxide purity and recovery in biogas. The complete mixing model was constructed in Mathcad and performance was optimized using Design Expert's Response Surface Methodology. The optimization of membrane technology in methane enrichment of biogas from a landfill in this project yield 100 % methane purity and recovery at CO2/CH4 selectivity of 623.12, stage cut of 0.43 and feed pressure of 3.79 bar using membrane configuration type 1 at methane concentration 0.53, CO2 permeability of 3871.00 barrer, CH4 permeability of 6.21 barrer, permeate pressure of 1 bar. This exceeded the performance of the previous work without staging the membrane process. At the methane composition of 0.60 in the feed gas, increasing the stage cut to 0.80 caused the purity of methane in retentate to be higher (100 %), but lower recovery of methane (37.97%). Feed pressure did not seem to affect the purity and recovery of methane in retentate significantly, but it caused carbon dioxide purity and recovery to slightly increase from 29.72 % to 46.20 % at the permeate side. When the methane composition in the feed was increased to 0.60, the 100 % purity of the methane in retentate was achieved whereas the recovery decreased to 37.97 %. The small error between previous work and the present study was 7 % and suggesting that the mode is highly accurate in forecasting the purity and recovery of the two gas species using the complete mixing model.